Wątki natury epistemologicznej i etycznej w staropolskiej refleksji nad retoryką i poezją na przełomie XVI i XVII wieku. Zagadnienia wybrane - Fischer, Jakub (My University, 2014)
Rozprawa doktorska jest propozycją ujęcia filozoficznych aspektów staropolskiej refleksji metaliterackiej na przełomie XVI i XVII wieku: wątków poznawczych i etycznych. Analiza tekstów źródłowych prowadzi do wyodrębnienia i opisania nadrzędnych idei tej refleksji – konweniencji i „dotknięcia rzeczy”. Idee te stanowią myślowe dominanty, istotne i trwałe w staropolskiej świadomości teoretycznoliterackiej: są fundamentem epistemologicznej i etycznej refleksji o retoryce i poezji, tworzą nadrzędną zasadę ładu i zgodności, decydującą o kształcie estetycznym dzieł literackich, o ich skuteczności komunikacyjnej i oddziaływaniu ideowym. Idee te określają teoretyczne ramy poznawczych i moralnych powinności sztuki słowa. Rozdziały I i II poświęcone są statusowi retoryki i poetyki w Polsce w drugiej połowie XVI wieku oraz teoretycznemu modelowi retoryki. Rozdział III przynosi analizę pism teoretycznoliterackich z przełomu XVI i XVII wieku. To dzieła trzech polskich teoretyków: Przydatki do „Polityki” Arystotelesowej i Przydatki do „Etyki” Arystotelesowej Sebastiana Petrycego z Pilzna, traktat Systema rhetoricae Bartłomieja Keckermanna, dwie prace Macieja Kazimierza Sarbiewskiego Characteres lyrici i De figuris sententiarum. Idee konweniencji i „dotknięcia rzeczy” służą wyjaśnianiu roli retoryki w budowaniu ładu życia społecznego oraz istoty retorycznego i poetyckiego poznania i działania. IV rozdział poświęcony jest porenesansowemu paradygmatowi sztuki słowa. Przedstawia on filozoficzne i esencjalistyczne ujmowanie literatury przez dawną refleksję teoretyczną oraz definicję człowieka jako istoty retorycznej.

The doctoral dissertation tends to analyse philosophical aspects of the Old Polish literary metareflection at the turn of the sixteenth and seventeenth centuries: all the cognitive and ethical topics. The analysis of source-based texts concentrates on question, which are the superior ideas of this reflection. These superior ideas: the idea of convenientia (agreement) and the idea of “touching things”, are both essential thought-features, significant and permanent in the Old Polish literary theory: they are the foundation of epistemological and ethical reflections on rhetoric and poetry, create a superior principle of harmony and order: determining factors of literary aesthetic. These ideas also take a decision about communication effectiveness and ideological influence of literary works: they define the theoretical frameworks of cognitive and moral obligations in literature. Chapters I and II are about the status of rhetoric and poetics in Poland in the second half of the sixteenth century, and about the theoretical model of rhetoric. Chapter III brings an analysis of the theoretical works of three Polish theorists at the turn of the sixteenth and seventeenth centuries: Appendages to the “Politics” of Aristotle and Appendages to the “Ethics” of Aristotle of Sebastian Petrycy, the treaty Systema rhetoricae of Bartholomew Keckermann, two treaties Characteres lyrici and De figuris sententiarum of Maciej Kazimierz Sarbiewski. Ideas convenientia and " touching things " explain the role of rhetoric in building the harmony of social life and explain the essence of rhetorical and poetic cognition and action. Chapter IV is about the post-renaissance paradigm of the rhetoric and poetics. It represents the essential and philosophical presentation of literature in the former theoretical reflections and the definition of man as a rhetorical being.
Epistemological and ethical topics in Old-Polish reflection on the rhetoric and poetry at the turn of the sixteenth and seventeenth centuries. Selected problems
Wydział Filologii Polskiej i Klasycznej
Keywords: retoryka; rhetoric; poetyka; poetics; konweniencja; agreement; renesans; Renaissance; barok; Baroque